A Herd of Wildebeest (Connochaetes taurinus) near the Mara river, in northern Serengeti, Tanzania - Kerr, Jeremy (Université d'Ottawa | University of Ottawa, 2019)
During the dry season, wildebeest undertake one of the largest mammal migrations on the planet, crossing from the drying plains of Serengeti across the Mara river into greener lands in Kenya. These wildebeest are nearing the final leg of that northward journey, approaching the Mara river. The wildebeest migration is iconic but few observers realize that it largely disappeared after the introduction of rinderpest into Africa, which decimated buffalo and wildebeest populations across the continent and exerted profound changes on fire regimes and savannah habitats over vast areas.
Keywords: Wildebeest; Savanna; Grassland; Field Course; Africa; African Ecology; OUPFB; Ontario Universities Program in Field Biology